The combined formulation of brassinolide and pyraclostrobin increases biomass and seed yield by improving photosynthetic capacity in Arabidopsis thaliana - An, Ya-Qi; Qin, Zi-Ting; Li, Dan-Dan; Zhao, Rui-Qi; Bi, Bo-Shi; Wang, Da-Wei; Ma, De-Jun; Xi, Zhen (Frontiers in Plant Science, 2023)
The unstable performance of brassinosteroids (BRs) in the field and the unavoidable phytotoxicity of pyraclostrobin (Pyr) limit their yield-enhancing effects. Furthermore, BRs applying in combination with Pyr has also promoted plant growth in several field trials. However, in addition to the benefits of disease control due to the innate fungicidal activity of Pyr, it remains to be understood whether the coapplication of BL+ Pyr exerts additional growth-promoting effects. For this purpose, the effects of BL treatment, Pyr treatment, and BL+ Pyr treatment in Arabidopsis thaliana were compared under pathogen-free conditions. The results showed that the yield increased at a rate of 25.6% in the BL+Pyr group and 9.7% in the BL group, but no significant change was observed in the Pyr group. Furthermore, the BL+Pyr treatment increased the fresh weight of both the leaves and the inflorescences. In contrast, the Pyr and BL treatments only increased the fresh weight of leaves and inflorescences, respectively. Furthermore, the Pn, Gs, Tr, Vcmax, Jmax, VTPU, ETR, and Rubisco enzyme activity increased by 26%, 38%, 40%, 16%, 19%, 15%, 9%, and 32%, respectively, with the BL + Pyr treatment and did not change significantly with the BL or Pyr treatments. Treatment with BL + Pyr and Pyr, rather than BL, improved the chlorophyll a and chlorophyll b contents by upregulating genes related to chlorophyll biosynthesis and downregulating genes related to chlorophyll degradation. Additionally, according to transcriptomic and metabolomic analysis, the BL+ Pyr treatment outperformed the individual BL or Pyr treatments in activating the transcription of genes involved in photosynthesis and increasing sugar accumulation. Our results first validated that the combined usage of BL and Pyr exerted striking synergistic effects on enhancing plant biomass and yield by increasing photosynthetic efficiency; thus, these results provide a scientific foundation for applying BL plus Pyr formulations to enhance yields in agriculture.